Comparação biológica, morfológica e molecular entre carrapatos do complexo Rhipicephalus sanguineus (Acari: Ixodidae) - Sanches, Gustavo Seron [UNESP] (2013)
The present study compares biological, morphological and molecular aspects of the adult stage of Rhipicephalus sanguineus ticks from different geographical regions of the world, such as Cuba (Havana), Brazil (Jaboticabal), Thailand (Bangkok), Argentina (Rafaela), and R. turanicus from Spain (Zaragoza). Furthermore, for R. sanguineus from Brazil (Jaboticabal) and R. turanicus from Spain (Zaragoza) the biological comparison were made for the immature stages, as well as the crossbreeding between these tick species. The larval stage of R. turanicus from Spain (Zaragoza) showed lower weight after feeding on rabbits when compared with R. sanguineus from Brazil (Jaboticabal). However, R. turanicus from Spain (Zaragoza) showed larger nymphs and adults due to a higher rate of growth, facilitated by greater intake of blood of these stages in relation to the R. sanguineus from Brazil (Jaboticabal). The crossbreeding between R. sanguineus from Brazil (Jaboticabal) and R. turanicus from Spain (Zaragoza) was not successful since the females crossed transpecifically produced a small amount of infertile eggs, indicating a separation between these two species. The comparison of biological parameters for the adult stage of the different populations showed differences, mainly in the weight of engorged females and in the engorgement period, also reflecting on the morphometric parameters of these species. The morphometric analysis suggests major similarity between R. sanguineus from Argentina (Rafaela) with R. turanicus from Spain (Zaragoza), also showing variations of size relative to populations of R. sanguineus from Cuba (Havana), Brazil (Jaboticabal) and Thailand (Bangkok). Morphologically, some differences were observed, especially in relation to the idiosoma shape, basis capituli shape and posterolatetal angles, females’ genital aperture and males’ spiracular plates, suggesting the occurrence of polymorphisms in different populations of R...